Meclofenoxate Inhibits Aggregation of Alpha-synuclein in vitro - Parui, Adhuna; Biswas, Soumojit; Roy, Ipsita (Protein and Peptide Letters, 2023)
Background: α-Synuclein, a natively disordered protein, is a key component of Lewy bodies, the ubiquitinated protein aggregates which are the pathological hallmark of Parkinson’s disease (PD). Meclofenoxate (centrophenoxine) is a nootropic drug which has shown beneficial therapeutic effects in various neuronal diseases. Administration of meclofenoxate enhanced levels of dopamine and improved motor function in animal models of Parkinson’s disease (PD). Evidence suggested that dopamine interacts with and modulates α-synuclein aggregation. Objective: The aim of this work was to investigate whether the observed positive effect of addition of meclofenoxate, a nootropic agent, on dopamine level, could be correlated with its effect on aggregation of α-synuclein. Methods: Purification of recombinant human α-synuclein was performed by anion exchange chromatography. The purified protein was incubated in the absence and presence of meclofenoxate and was analyzed for aggregation by Thioflavin T fluorescence spectroscopy. Conformational changes in α-synuclein were monitored by fluorescence spectroscopy and fluorescence quenching studies using a neutral quencher. Secondary structure analysis of α-synuclein was monitored by circular dichroism spectroscopy. Results: Recombinant human α-synuclein was expressed and purified by anion-exchange chromatography. Incubation of α-synuclein with meclofenoxate led to lowering aggregation in a concentration-dependent manner. Reduction in formation of oligomers was seen which suggested the formation of an off-pathway species which did not give rise to an aggregation-competent entity. Fluorescence quenching studies revealed that the additive distorted the native conformation of α- synuclein, leading to the formation of lower amounts of aggregation-prone species. Conclusion: In the presence of higher concentrations of meclofenoxate, α-synuclein undergoes a change in its conformation. This change is not dependent on the concentration of the additive. This non-native conformer promotes the formation of a species which does not undergo further aggregation. Our study provides a mechanistic explanation of the earlier observation that meclofenoxate has a beneficial effect on progression of PD in animal models.
Keywords: oligomers